Causes Behind the Pulwama Attack: Political Implication to Asymmetry Agenda: Pulawama Attack, Indian Security Forces (ISFs), Propaganda, Kashmir, Political and Strategic War - khan, Samiullah; Dr. Haseeb ur Rehman; Muhammad Rehman; Khan, Dr. Rooh ul Amin (Journal of Peace, Development and Communication, 2020)
This article focuses on the conflicted relationship between two neighboring nuclear powers, Pakistan and India. The Kashmir dispute has created intense relations not for both countries also for the South Asian region. After industrialization and globalization, every country demands peace, prosperity, and sustainable development in the region but bad diplomatic relations between any two countries can ruin the development and peace process in the region. In South Asia, two atomic countries are not able to dissolve their issues since independence and even they are eager to sacrifice their own interest/benefit to harm each other. In different UN Peace mission both countries deliver their best for the peace, harmony, and prosperity for the world but not ready to promote peace in their reign. This article based on Pulwama Attack that opened new doors for political, strategic, economic wars and closed doors for political economy, trade, development, financial prosperity, and peace. Moreover, this article explores the media role to mold the facts and disperse asymmetrical information for their personal or political interest without analyzing the consequences of asymmetry agenda. Besides all the disputes and wars some questions have been raised in this article: Is Kashmir dispute open new contention for both states? What were the consequences of pre and post-Pulwama Attack? Can ever be diplomatic relations and foreign policies of both countries friendly? Will both countries secure their mutual interest and decision-makers work for the prosperity of their own people instead of blaming each other in the international forums? How long both countries will live with their disputes without any proper solution?